Usability and accessibility assessment of the WWF-Philippines' Coastal and Marine Resources Information System (CMARIS) - Villarta, Peter Julius C.; Jamin, Raymond P. (Quezon City Institute of Library and Information Science, University of the Philippines Diliman, 2006)
Computer-based information systems are now prevalent in this day and age. They are now serve various specialized purpose, deployed and accessible via several means, and is practically evident in all fields of endeavor.
The Coastal and Marine Resources Information System (CMARIS) is one such system. It was designed to serve information relevant to environmental protection and conservation and is accessible to a wide-range of users over the Internet. This study is an investigation on how effectively the CMARIS met its original design objective with particular focus on usability and accessibility issues as a consequential factor in the overall success of the CMARIS in meeting the said objective.
The system's usability and accessibility qualities were reviewed and set against standards set by the usability and accessibility authorities and experts. At the same time, an online user survey was launched to collect information on user demographics, usage statistics, as well as user perceptions on various aspects of the system. The result of the survey are later juxtaposed with the results of the assessment for analysis.
The assessment reveal the CMARIS to have no serious issues in both usability and accessibility, which is further reinforced by the generally positive feedback by users on aspects concerning these two qualities. However, overall user rating of the CMARIS is relatively low despite high ratings on its usability and accessibility qualities.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Coastal and Marine Resources Information System (CMARIS).; Computer systems